Teknologi Reproduksi: Bayi Tabung dan Peran Rahim Pengganti - Luthfia Rizky Amanda Tjoei; Vika Jeny Putri Anastasya (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
This article discusses the advancement of reproductive technology, especially in vitro fertilization (IVF) and surrogate motherhood, and their legal, ethical, and religious implications. IVF and surrogate motherhood are technologies that offer solutions for couples facing infertility problems, but also pose major challenges in social and moral aspects. This article uses a descriptive approach to analyze various perspectives related to these practices, including the Islamic view that tends to allow IVF with certain conditions, but rejects surrogate motherhood. This study finds that although reproductive technology offers new hope, it is important to adjust regulations by considering legal, medical, and religious values ​​so that this technology can be applied wisely and humanely.